Abstract: The aims of the resear THE EFFECT OF BRAINSTORMING METHOD IN TEACHING WRITING SHORT STORY ON STUDENTS' WRITING SHORT STORY (A STUDY AT THE ELEVENTH GRADE OF SMS NEGERI 1 PAHAE JULU IN 2019/2020 ACADEMIC YEAR) - Putri Tania Sianturi (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The aims of the research to know the extent of the application of brainstorming method in teaching writing short story, the extent of the students’ writing short story before and after using brainstorming method, and to know whether there is any significant effect of brainstorming method on students’ writing short story at the eleventh grade of SMA Negeri 1 PahaeJulu. The research is conducting by using experimental method (pretest posttest one group design) with 32 students as the sample and they are taking by using random sampling technique from 124 students as population. Test and observation are using in collecting the data. Based on the data analysis, it can be find the average of application of brainstorming method in teaching writing short story is 3.10 categorized “good”, and the average of students’ writing short story before and after using brainstorming method at the eleventh grade of SMA Negeri 1 PahaeJulu was 66.44 categorized “enough” and 77.13 categorized “good”. Furthermore, based on inferential statistic by using ttest, the writer find ttest less than ttable (5.34 > 1.309). It means, there is a significant effect of using brainstorming method on students’ writing short story at the eleventh grade of SMA Negeri 1 PahaeJulu.”.